Molecular Regulation of Carotenoid Accumulation Enhanced by Oxidative Stress in the Food Industrial Strain Blakeslea trispora - Jiawei Deng; Yuyang Chen; Siting Lin; Yilu Shao; Yuan Zou; Qianwang Zheng; Liqiong Guo; Junfang Lin; Moutong Chen; Zhiwei Ye (Foods)
Blakeslea trispora is a key industrial strain for carotenoid production due to its rapid growth, ease of cultivation, and high yield. This study examined the effects of oxidative stress induced by rose bengal (RB) and hydrogen peroxide (H2O2) on carotenoid accumulation, achieving maximum yields of 459.38 ± 77.15 μg/g dry cell weight (DCW) at 0.4 g/L RB and 294.38 ± 14.16 μg/g DCW at 0.6% H2O2. These results demonstrate that oxidative stress promotes carotenoid accumulation in B. trispora. To investigate the underlying molecular mechanisms, transcriptional levels of key genes were analyzed under optimal stress conditions. In the carotenogenic pathway, only HMGR showed upregulation, while ACC, linked to fatty acid biosynthesis, remained unchanged. Within the mitogen-activated protein kinase (MAPK) pathway, FUS3 transcription increased under both stress conditions, MPK1 transcription rose only under H2O2 stress, and HOG1 exhibited no significant changes. Among heat shock proteins (HSPs), only HSP70 showed elevated transcription under H2O2 stress, while other HSP genes remained unchanged. These findings suggest that oxidative stress induced by RB and H2O2 enhances carotenoid accumulation in B. trispora through distinct regulatory pathways. This study provides valuable insights into stress-adaptive mechanisms and offers strategies to optimize carotenoid production in fungi.